The impact of conference attendance on Australian academic librarians and libraries - Dumbell, Petra (Curtin University, 2019)
The focus of this research project is the impact of conference attendance, in the context of Australian academic librarians and libraries. The impact of conference attendance is shown to consist of three key themes: informational; social; and affective impact. In addition, the study found nine factors that can influence the impact conference attendance can have on the delegate and on their institution, and it presents connections between key themes of impact and influencing factors.